Biking signal / Muhammad Asyraf Ismail and Muammar Hanafi Mohd Kadiman - Ismail, Muhammad Asyraf; Mohd Kadiman, Muammar Hanafi (2015)
This project develops for bikers that always going to an event at night with their club or their friends. This waterproof bag signal will help people know where you're headed when you're biking, we named this project as Turn Signal Biking Bag. This will increasing the safety of the bikers and prevents an accident to the bikers. We'll use single core wire as replacement to conductive thread and Velcro are applied to the jacket and the bag so its will wearable and washables when you're done. This project use Lily Pad Arduino Main Board to install program instruction to conduct this system properly. We use LED as a signal and 2 button push to complete our circuit. And to let the user know which their jacket function or not, we put audio output, buzzer, so if the buzzer buzzing that means the jacket is functioning.